Analisis Korelasi Logistik Profitabilitas, Leverage, Serta Likuiditas Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Anna Apriana Hidayanti; Nungki Kartikasari (Valid: Jurnal Ilmiah, 2023)
This study aims to analyze the factors that affect the timeliness of submitting financial reports of manufacturing companies in Indonesia. With the factors referred to in this study are profitability, leverage and liquidity as independent variables while timeliness as the dependent variable. The sample of this study consisted of 62 companies listed on the Indonesia Stock Exchange (IDX) and submitted financial reports to the OJK in the 2018-2019 period. The type of data used in this study is quantitative data and the data source used is secondary data. The sample of this study was selected using purposive sampling and stratified random sampling methods. The analytical tool in this research is logistic regression analysis at a significance level of 5%. The results of hypothesis testing show that profitability and liquidity have a significant positive effect on the timeliness of financial report submission. However, leverage has a positive and insignificant effect on the timeliness of financial report submission